Certification and Lecturers’ Performance in State Polytechnic: a Mediating Role of Psychological Empowerment - Wahyu, Ellyn Eka; Senja Oktora, Yekie; Ery Octalina, Lydia (Jurnal Bisnis dan Manajemen, 2024)
This research aims to test and analyze the influence of certification on lecturer performance which is mediated by the psychological empowerment variable. The population in this study were lecturers majoring in commercial administration at the Malang State Polytechnic with a sample size of 66 respondents determined using the Krecjie Morgan table with probability sampling characteristics. The data collection method was carried out by distributing offline questionnaires, then for path analysis using SEM based on SMARTPLS version 3. The research results showed that certification had an effect on psychological empowerment. Psychological empowerment influences lecturers' performance. Certification has no effect on lecturers' performance. The model proposed in this research suggests reviewing the use of renewable learning media to support lecturer performance.